Réflexions autour de l'institutionnalisation des disciplines - Robert Boure (Communication)
Starting from a portrait of discourses held on the institutionalization of two disciplines which seem completely opposed — the sciences of information and communication, and economics — this article puts the largely held assumption in the French scientific field that there exists a « normal » mode of institutionalization of disciplines which allows us to endow them with the label of scientific into question. The paper proposes another « way of doing » which might lead the way to a research program in which certain dimensions may be rapidly put to work in the French sciences of information and communication.